PENGARUH TIPE KEPRIBADIAN KOMITMEN ORGANISASI MOTIVASI TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA PETUGAS DI TAMAN WISATA ALAM KAWAH IJEN - Trigunajasa, Sunandar; Sularso, Raden Andi; Titisari, Purnamie (BISMA: Jurnal Bisnis dan Manajemen, 2017)
Abstract: This study aims: (1) to analyze the influence of personality type to the Organization Citizenship Behavior (OCB) in Ijen Crater Natural Park; (2) to analyze the influence of the organization's commitment to the Organization Citizenship Behavior (OCB) in Ijen Crater Natural Park; (3) to analyze the influence of motivation to the Organization Citizenship Behavior (OCB) in Ijen Crater Natural Park; (4) to analyze the influence of personality type on the performance of officers in Ijen Crater Natural Park; (5) to analyze the effect of organizational commitment on performance of staff in Ijen Crater Natural Park; (6) to analyze the influence of motivation on the performance of officers in Ijen Crater Natural Park; (7) to analyze the Organization Citizenship Behavior (OCB) on the performance of officers in Ijen Crater Natural Park. The number of samples taken are 35 respondents (the employees of KSDA Sector Region III Jember, Conservation Section Region V Banyuwangi, Conservation Resort Region 18 Kawah Ijen).Result of the study indicates that (1) the officer's personality type has positive effect but not significant on the Organization Citizenship Behavior (OCB) in Ijen Crater Natural Park.; (2) organizational commitment has significant positive effect on the Organization Citizenship Behavior (OCB) in the Ijen Crater Natural Park. (3) officers motivation has positive effect but not significant on the Organization Citizenship Behavior (OCB) in Ijen Crater Natural Park.; (4) personality type has significant positive effect on the performance of officers in Ijen Crater Natural Park; (5) organizational commitment has significant positive effect on the performance of officers in Ijen Crater Natural Park; (6) motivation has positive effect but not significant on the performance of officers in Ijen Crater Natural Park; (7) Organization Citizenship Behavior (OCB) has positive and significant impact on the performance of officers in Ijen Crater Natural Park. Keywords: Ijen Crater Natural Park, Personality Type, Organization Commitment, Motivation, Organization Citizenship Behavior (OCB), Performance;